Pengaruh Customer Relationship Terhadap Loyalitas Nasabah Tabungan Batara Pada PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Padang - Sri Rahayu Chandra (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate This research was conducted to prove the effect of communication, satisfaction, commitment and trust in batara savings customer loyalty at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch Office. There are 70 customers who have balances above Rp. 100,000,000 for the past 1 year with sample criteria, have been BTN customers for at least 3 years with a minimum age of 17 years at BTN Padang. Data were collected using a questionnaire. Furthermore, this study uses multiple linear regression analysis supported by the SPSS program. The results of the study indicate that communication, satisfaction, commitment and trust have a positive and significant effect on customer loyalty of batara savings at PT. Bank Tabungan Negara (Persero) tbk Padang Branch Office